2018
DOI: 10.17159/sajs.2018/4407
|View full text |Cite
|
Sign up to set email alerts
|

Food insecurity, HIV status and prior testing at South African primary healthcare clinics

Abstract: HIV and food insecurity are two prominent causes of morbidity and mortality in sub-Saharan Africa. Food insecurity has been associated with risky sexual practices and poor access to healthcare services. We describe the association between household food insecurity and previous HIV testing and HIV status. We used logistic regression to analyse the association between food insecurity and prior HIV counselling and testing (HCT) and testing HIV positive. A total of 2742 adults who presented for HCT at three primar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 24 publications
0
2
0
Order By: Relevance
“…We found that the majority of participants experienced food insecurity during the lockdown time. Food insecurity among MSM has been shown to be associated with lower rates of HIV testing (Nyirenda et al, 2018 ; Takada et al, 2020 ; Weinhardt et al, 2017 ; Wiss et al, 2021 ), higher new HIV infection (Amon Exavery et al, 2020 ), and potential violence in the community (Adhikari et al, 2020 ). It is important to improve the access to food secure care programs.…”
Section: Discussionmentioning
confidence: 99%
“…We found that the majority of participants experienced food insecurity during the lockdown time. Food insecurity among MSM has been shown to be associated with lower rates of HIV testing (Nyirenda et al, 2018 ; Takada et al, 2020 ; Weinhardt et al, 2017 ; Wiss et al, 2021 ), higher new HIV infection (Amon Exavery et al, 2020 ), and potential violence in the community (Adhikari et al, 2020 ). It is important to improve the access to food secure care programs.…”
Section: Discussionmentioning
confidence: 99%
“…This finding is consistent with several others. [28][29][30] One of the possible mechanisms responsible for food insufficiency is that while concentrating on taking care of the OVC, the caregiver may not always have adequate time to participate in food production activities such as farming or income generating businesses. 31 Since lack of adequate food increases HIV risk behaviors, 32 the likelihood of HIV infection increases as well.…”
Section: Discussionmentioning
confidence: 99%